Baseline distribution and sources of linear alkyl benzenes (LABs) in surface sediments from Brunei Bay, Brunei - Alkhadher, S.A.A.; Zakaria, M.P.; Yusoff, F.M.; Kannan, N.; Suratman, S.; Keshavarzifard, M.; Magam, S.M.; Masood, N.; Vaezzadeh, V.; Sani, M.S.A. (2015)
Sewage pollution is one of major concerns of coastal and shoreline settlements in Southeast Asia, especially Brunei. The distribution and sources of LABs as sewage molecular markers were evaluated in surface sediments collected from Brunei Bay. The samples were extracted, fractionated and analyzed using gas chromatographymass spectrometry (GC-MS). LABs concentrations ranged from 7.1 to 413 ng g(-1) dry weight (dw) in surficial sediments from Brunei Bay. The study results showed LABs concentrations variably due to the LABs intensity and anthropogenic influence along Brunei Bay in recent years. The ratio of Internal to External isomers (I/E ratio) of LABs in sediment samples from Brunei Bay ranged from 0.56 to 2.17 along Brunei Bay stations, indicating that the study areas were receiving primary and secondary effluents. This is the first study carried out to assess the distribution and sources of LABs in surface sediments from Brunei Bay, Brunei. (C) 2015 Elsevier Ltd. All rights reserved.